A natural fiber pipeline composite aerogel catalyst
By combining wood powder with catalytic ions, a natural fiber pipeline composite aerogel catalyst is formed, which solves the problem of existing catalysts being easily worn, denaturated and inactivated under high temperature and high pressure conditions, and achieves high-efficiency, low-cost, and environmentally friendly catalytic effects .
Patent Information
- Application Number
- CN202310256621.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing aluminum, iron and zinc-based catalysts have uneven void distribution and columnar particles lead to insufficient utilization of the inner and outer surfaces, and are prone to wear and denaturation and inactivation under high temperature and high pressure conditions.
By combining wood powder with catalytic ions, a natural fiber pipeline composite aerogel catalyst is formed, and the natural holes and high toughness of wood powder are used to form a new catalyst with high temperature resistance, high catalytic, low cost and environmentally friendly.
The efficient utilization of the catalyst is achieved, the reaction efficiency and catalytic activity are improved, the cost is reduced, and the stability and wear resistance are maintained under high temperature conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation, and in particular relates to a natural fiber pipeline composite aerogel catalyst and a preparation method thereof. Technical Background
[0002] Catalysts are "essentials" in many chemical reactions. They can effectively degrade the activation energy in the reaction process, greatly reduce energy consumption, and quickly promote the formation of products. Aluminum, iron, and zinc-based catalysts are widely used due to their affordable prices and ease of use. However, these types of catalysts currently have uneven distribution of voids, and they are usually columnar particles, which makes it impossible to fully utilize their inner and outer surfaces, thus affecting the overall reaction efficiency. At the same time, during the generation process of columnar catalysts, due to the influence of pressure and temperature, they will experience large fluctuations. Large airflows and high temperatures will cause friction between the solutions of the particles, causing the catalyst to wear, denature, and eventually become inactivated.
[0003] Compared with coal and other energy sources, wood powder has a shorter growth cycle and has natural holes for plants to breathe and transport nutrients. It is mainly formed by the entanglement of lignin, cellulose and hemicellulose. It is precisely because of this formation principle that wood has high toughness and strong shear resistance.
[0004] Therefore, the inventors have proposed a conception, that is, based on the high-efficiency catalytic characteristics of aluminum, iron, zinc and other catalysts and the natural porosity, high toughness and strong shear resistance of wood, a new material of composite catalyst that can realize aluminum, iron and zinc-based catalysis and combine the natural pores of wood to be stable at high temperatures, not easy to break, low cost and environmentally friendly is developed.
[0005] The inventors found that in the currently available literature and data records, the structural characteristics of wood powder are that cellulose, lignin, and hemicellulose are intertwined to form a natural organic polymer structure, which has the characteristics of high toughness and easy growth. The catalyst has the characteristics of fast reaction rate, unchanged quality before and after the reaction, and the characteristics of natural holes provide an excellent reaction space for the catalyst. The short growth period of wood powder and the relatively low cost can reduce a lot of capital investment for enterprises, and the high toughness also provides great convenience for installation and transportation, while reducing transportation risks. Summary of the invention
[0006] The purpose of the present application is to provide a natural fiber pipeline composite aerogel catalyst, the preparation method of which combines the catalyst with the natural fiber channel to form a new catalyst that is resistant to high temperature, highly catalytic, low-cost, environmentally friendly, and has three-dimensional highly complexed pores that are interconnected.
[0007] The technical solution of the present invention:
[0008] Raw material preparation and wood powder pretreatment:
[0009] Step 1: Crush the wood and then boil it. After boiling, put it into a drying oven to dry it, so as to increase its contact surface and effectively remove surface impurities;
[0010] Removal of lignin and hemicellulose from internal impurities:
[0011] Step 2: putting the dried wood powder into a sodium hydroxide solution for boiling, and drying after boiling, wherein the concentration of the sodium hydroxide solution is 1 mol / l to 5 mol / l;
[0012] Step 3: After the wood powder obtained in step 2 is dried, it is placed in a mixed solution of sodium hydroxide and ethanol and boiled. After completion, the wood powder is rinsed and dried, and then soaked in deionized water;
[0013] Catalytic ion attachment:
[0014] Step 4: soaking the delignified wood powder obtained in step 3 in a sodium isophthalate sodium silicate solution, and drying after soaking; the concentration of the sodium silicate solution is 1 mol / l to 3 mol / l, and the concentration of the sodium isophthalate solution is 0.5 mol / l to 3 mol / l;
[0015] Step 5: Mix phosphoric acid solution, ferric chloride solution, aluminum chloride solution and zinc oxide solution of a certain concentration, and then put the wood powder of step 4 into the mixture for soaking at a certain temperature; the phosphoric acid concentration is 10% to 85%, the ferric chloride solution concentration is 0.5 mol / l to 3 mol / l, the aluminum chloride solution concentration is 0.5 mol / l to 3 mol / l, the zinc oxide solution concentration is 0.5 mol / l to 3 mol / l, and the temperature setting range is 25°C to 90°C;
[0016] Step 6: Dry the product of step 5 under the protection of a nitrogen atmosphere with a certain flow rate to obtain a natural fiber pipeline composite aerogel catalyst, wherein the nitrogen flow rate is 0.5 to 3 m / s.
[0017] Furthermore, the boiling time in step 1 is 0.5 h to 2 h, the drying time is 2 h to 6 h, and the drying temperature is 60° C. to 90° C.
[0018] Furthermore, the boiling time in step 2 is 12 h to 48 h, the drying time is 0.5 h to 2 h, and the drying temperature is 60° C. to 90° C.
[0019] Furthermore, in the mixed solution of sodium hydroxide and ethanol in step 3, sodium hydroxide solution is mainly used as the main component and ethanol is added, the concentration is 15% to 20%, the soaking time is 12h to 24h, the boiling time is 2h to 12h, the drying temperature is 60°C to 90°C, and the drying time is 0.5h to 4h.
[0020] Furthermore, in step 4, the soaking time is 3 to 6 hours, the drying time is 1 to 2 hours, and the drying temperature is 60° C. to 90° C.
[0021] Furthermore, the soaking time in step 5 is 6 to 12 hours.
[0022] Furthermore, in step 6, the drying time is 12 hours to 24 hours, and the drying temperature is 80° C. to 150° C.
[0023] The present invention enables the catalyst and the natural fiber pipeline to form a new catalyst which is high temperature resistant, highly catalytic, low cost, environmentally friendly, and has three-dimensional highly complexed interconnected pores. DETAILED DESCRIPTION
[0024] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the range is specifically disclosed. Example
[0025] A natural fiber pipeline composite aerogel catalyst, the preparation method of which comprises the following steps:
[0026] Raw material preparation and wood powder pretreatment:
[0027] Step 1: Boil the wood powder obtained after crushing for 30 minutes, put it into a drying oven after boiling and set the temperature to 60°C for 2 hours to effectively remove surface impurities.
[0028] Removal of internal impurities (lignin, hemicellulose) stage:
[0029] Step 2: The dried wood powder is placed in a sodium hydroxide solution with a concentration of 1 mol / l and boiled for 12 hours and then dried at a temperature of 60° C. for 30 minutes.
[0030] Step 3: The wood powder obtained in step 2 is soaked in deionized water for 12 hours. After drying, it is placed in a mixed solution of sodium hydroxide and ethanol at a certain concentration and boiled for 2 hours. The mixed concentration is 15%. After completion, the wood powder is rinsed and dried at 60°C for 30 minutes.
[0031] Catalytic ion attachment:
[0032] Step 4: The delignified wood powder obtained in step 3 is immersed in a mixed solution of 1 mol / l sodium silicate solution and 1 mol / l sodium isophthalate, and dried at 60° C. for 1 hour after the immersion is completed.
[0033] Step 5: Mix 70% phosphoric acid concentration, 0.5 mol / l ferric chloride solution, 0.5 mol / l aluminum chloride solution, and 0.5 mol / l zinc oxide solution, and soak the wood powder obtained in step 4 at 25°C for 6 hours and dry at 60°C for 30 minutes.
[0034] Step 6: Dry the wood powder obtained in step 7 at 80° C. for 12 h under the protection of a nitrogen atmosphere with a flow rate of 0.5 m / s to obtain a natural fiber pipeline composite aerogel catalyst.
[0035] The surface microstructure analysis of the natural fiber pipeline composite aerogel catalyst obtained through the above implementation cases was carried out on a Hitachi S-4700 field emission scanning electron microscope; the specific surface area, pore size distribution and pore volume of the aerogel were characterized by a NOVA4200e specific surface and porosity analyzer, and the density of the aerogel was calculated by the drainage method. The obtained characterizations are: the specific surface area is 682m2 / g, the pore size is 23nm, and the density is 0.335g / cm3. It is also used in the dehydration of methanol to dimethyl ether. At 280℃ and one atmosphere, methanol (ω(CH3OH)﹥99.9%) is used as feed, and it enters the reactor after being metered by a 2PB-00C type horizontal flow pump. An isothermal integral reactor is used, and the vaporized methanol undergoes a dehydration reaction in the catalyst bed. The gas after the reaction enters the condenser through a back pressure valve, where water and methanol are condensed. The condensate is weighed by sampling at regular intervals, and the tail gas after the condenser is measured by a soap film flowmeter. Agilent GC6820 thermal conductivity detector was used to analyze water and organic matter, and the organic matter was mainly methanol and dimethyl ether; Agilent GC6890N hydrogen flame ionization detector was used to analyze methanol and dimethyl ether. The results showed that the methanol conversion rate was 94.93%, and the maximum dimethyl ether yield could reach 21.63g / (g·h). Example
[0036] A natural fiber pipeline composite aerogel catalyst, the preparation method of which comprises the following steps:
[0037] Raw material preparation and wood powder pretreatment:
[0038] Step 1: Boil the wood powder obtained after crushing for 1 hour, put it into a drying oven after boiling and set the temperature to 70°C for 2 hours to effectively remove surface impurities.
[0039] Removal of internal impurities (lignin, hemicellulose) stage:
[0040] Step 2: The dried wood powder is placed in a 2 mol / l sodium hydroxide solution and boiled for 16 hours and then dried for 1 hour.
[0041] Step 3: The wood powder obtained in step 2 is soaked in deionized water for 16 hours. After drying, it is placed in a mixed solution of sodium hydroxide and ethanol at a certain concentration and boiled for 6 hours. The mixed concentration is 17%. After completion, the wood powder is rinsed and dried at 70°C for 1 hour.
[0042] Catalytic ion attachment:
[0043] Step 4: The delignified wood powder obtained in step 3 is immersed in a mixed solution of 1 mol / l sodium silicate solution and 0.5 mol / l sodium isophthalate, and dried at 60° C. for 2 h after the immersion is completed.
[0044] Step 5: Mix 50% phosphoric acid concentration, 1 mol / l ferric chloride solution, 1 mol / l aluminum chloride solution, and 1 mol / l zinc oxide solution, and then soak the wood powder obtained in step 6 at 50°C for 9 hours and dry at 70°C for 30 minutes.
[0045] Step 6: Dry the wood powder obtained in step 7 at 80° C. for 12 h under a nitrogen atmosphere with a flow rate of 1 m / s to obtain a natural fiber pipeline attached hybrid ion catalyst.
[0046] The surface microstructure analysis of the natural fiber pipeline composite aerogel catalyst obtained through the above implementation cases was carried out on a Hitachi S-4700 field emission scanning electron microscope; the specific surface area, pore size distribution and pore volume of the aerogel were characterized by a NOVA4200e specific surface and porosity analyzer, and the density of the aerogel was calculated by the drainage method. The obtained characterizations are: the specific surface area is 735m2 / g, the pore size is 25nm, and the density is 0.307g / cm3. It is also used in the dehydration of methanol to dimethyl ether. At 280℃ and one atmosphere, methanol (ω(CH3OH)﹥99.9%) is used as feed, and it enters the reactor after being metered by a 2PB-00C type horizontal flow pump. An isothermal integral reactor is used, and the vaporized methanol undergoes a dehydration reaction in the catalyst bed. The gas after the reaction enters the condenser through a back pressure valve, where water and methanol are condensed. The condensate is weighed by sampling at regular intervals, and the tail gas after the condenser is measured by a soap film flowmeter. Agilent GC6820 thermal conductivity detector was used to analyze water and organic matter, and the organic matter was mainly methanol and dimethyl ether; Agilent GC6890N hydrogen flame ionization detector was used to analyze methanol and dimethyl ether. The results showed that the methanol conversion rate was 96.32%, and the maximum dimethyl ether yield could reach 23.72g / (g·h). Example
[0047] A natural fiber pipeline composite aerogel catalyst and a preparation method thereof, wherein the preparation method comprises the following steps:
[0048] Raw material preparation and wood powder pretreatment:
[0049] Step 1: Boil the wood powder obtained after crushing for 2 hours, put it into a drying oven after boiling and set the temperature to 90°C for 6 hours to effectively remove surface impurities.
[0050] Removal of internal impurities (lignin, hemicellulose) stage:
[0051] Step 2: The dried wood powder is placed in a 5 mol / l sodium hydroxide solution and boiled for 48 hours, followed by drying for 2 hours.
[0052] Step 3: The wood powder obtained in step 2 is soaked in deionized water for 24 hours. After drying, it is placed in a mixed solution of sodium hydroxide and ethanol at a certain concentration and boiled for 6 hours. The mixed concentration is 20%. After completion, the wood powder is rinsed and dried at 90°C for 4 hours.
[0053] Catalytic ion attachment:
[0054] Step 4: The delignified wood powder obtained in step 3 is immersed in a mixed solution of 1 mol / l sodium silicate solution and 2 mol / l sodium isophthalate, and dried at 60° C. for 1 hour after the immersion is completed.
[0055] Step 5: Mix 30% phosphoric acid concentration, 3 mol / l ferric chloride solution, 3 mol / l aluminum chloride solution, and 3 mol / l zinc oxide solution, and soak the wood powder obtained in step 6 at 75°C for 12 hours and dry at 90°C for 1 hour.
[0056] Step 6: Dry the wood powder obtained in step 7 at 150° C. for 24 hours under a nitrogen atmosphere with a flow rate of 3 m / s to obtain a natural fiber pipeline attached hybrid ion catalyst.
[0057] The surface microstructure analysis of the natural fiber pipeline composite aerogel catalyst obtained through the above implementation cases was carried out on a Hitachi S-4700 field emission scanning electron microscope; the specific surface area, pore size distribution and pore volume of the aerogel were characterized by a NOVA4200e specific surface and porosity analyzer, and the density of the aerogel was calculated by the drainage method. The obtained characterizations are: the specific surface area is 702m2 / g, the pore size is 24nm, and the density is 0.327g / cm3. It is also used in the dehydration of methanol to dimethyl ether. At 280℃ and one atmosphere, methanol (ω(CH3OH)﹥99.9%) is used as feed, and it enters the reactor after being metered by a 2PB-00C type horizontal flow pump. An isothermal integral reactor is used, and the vaporized methanol undergoes a dehydration reaction in the catalyst bed. The gas after the reaction enters the condenser through a back pressure valve, where water and methanol are condensed. The condensate is weighed by sampling at regular intervals, and the tail gas after the condenser is measured by a soap film flowmeter. Agilent GC6820 thermal conductivity detector was used to analyze water and organic matter, and the organic matter was mainly methanol and dimethyl ether; Agilent GC6890N hydrogen flame ionization detector was used to analyze methanol and dimethyl ether. The results showed that the methanol conversion rate was 95.42%, and the maximum dimethyl ether yield could reach 22.83g / (g·h).
[0058] The present invention combines the catalyst with the natural fiber channels to form a novel catalyst which is high temperature resistant, highly catalytic, low cost, environmentally friendly, and has three-dimensional highly complexed interconnected pores.
[0059] The implementation cases described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A natural fiber pipeline composite aerogel catalyst, characterized in that: The preparation method comprises the following steps: Raw material preparation and wood powder pretreatment: Step 1: Boil the wood powder obtained after pulverization for 1 hour, and then put it into a drying oven at a set temperature of 70°C for 2 hours to effectively remove surface impurities; Removal of internal lignin and hemicellulose stage: Step 2: Put the dried wood powder into a 2 mol / L sodium hydroxide solution for boiling, and then dry it for 1 hour after boiling for 16 hours; Step 3: Soak the wood powder obtained in step 2 in deionized water for 16 hours, and then put it into a mixed solution of sodium hydroxide and ethanol at a certain concentration and boil it for 6 hours after drying. The concentration of the mixed solution is 17%. After completion, rinse the wood powder and dry it at 70°C for 1 hour. Aerogel composite: Step 4: immerse the wood powder obtained in step 3 in a mixed solution of 1 mol / L sodium silicate solution and 0.5 mol / L sodium isophthalate, and dry at 60° C. for 2 h after immersion; Step 5: Mix 50% phosphoric acid solution, 1 mol / L ferric chloride solution, 1 mol / L aluminum chloride solution and 1 mol / L zinc oxide solution, and soak the wood powder obtained in step 4 at 50°C for 9 hours and dry at 70°C for 30 minutes; Step 6: Dry the wood powder obtained in step 5 at 80° C. for 12 h under a nitrogen atmosphere with a flow rate of 1 m / s to obtain a natural fiber pipeline composite aerogel catalyst.
Citation Information
Patent Citations
Porous hydrogel with slow release function and preparation method thereof
CN112939679A
Organic aluminum-SiO2 type aerogel-like catalyst and preparation method thereof
CN115591585A